Method development and validation for the determination of residual solvents in quinabut API by using gas chromatography. Message 2 - Оlena Golembiovska; Oleksii Voskoboinik; Galina Berest; Sergiy Kovalenko; Liliya Logoyda (Pensoft Publishers, 2021)
Aim. The aim of study was to develop and validate a simple, precise and accurate method using gas chromatography for analysis of residual solvents - acetone and 2-propanol - in quinabut API. Materials and methods. All experiments were performed on a gas chromatographic system equipped with FID detector (Shimadzu GC System) using the DB-624 (30 m × 0.32 mm ID, 3.0 μm film sickness) column as stationary phase. Nitrogen was used as carrier gas with flow rate 7.5 mL/ min. Split ratio was 1:5, injector temperature was 140 °C, detector temperature was 250 °C, oven temperature was programmed from 40 °C (2 min) to 50 °C at 1 °C/min and then increased at a rate of 15 °C/min up to 215 °C; and maintained for 2 min. All solutions were prepared using water as diluent. Results. This proposed method is assessed for separation of residual solvent from quinabut with quantification. The obtained results are compared with the corresponding specified limits of ICH standard guidelines. The method validation was done by evaluating specificity, limit of detection (LOD) and limit of quantitation (LOQ), linearity, accuracy, repeatability, ruggedness, system suitability and method precision of residual solvents as indicated in the ICH harmonized tripartite guideline. The separation between acetone and 2-propanol peaks is 2.07. Hence method was found to be specific. The linear relationship evaluated across range of 15 to 180% for acetone and 2-propanol of ICH specified limit of residual solvents. The graphs of theoretical concentration versus obtained concentration are linear and the regression coefficients 'R' for residual solvents were more than 0.9968. The values of LOD and LOQ were much less than the lower limit of the concentration range and cannot affect the accuracy of the test. The technique was characterized by high intra-laboratory accuracy at concentrations close to the nominal acetone and 2-propanol concentration. All solutions were stable in water for at least 1 hour when stored at room temperature. Conclusion. A simple, specific, accurate, precise and rugged gas chromatography method was developed and validated for the quantification of residual solvents present in quinabut API through an understanding of the synthetic process, nature of solvents and nature of stationary phases of columns. The residual solvents acetone and 2-propanol were determined.